THE "PRIMORDIAL PATRON" OR "MENTOR" ARCHETYPES OF THE MYTHOLOGICAL WORLD - Zh.A. Aymukhambet, A.A. Mirzakhmetov, S. Aituganova, R.M. Mukhazhanova, Zh. Karipbaev (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article focuses on the relation between the protagonist and the mentor, which is so often seen in folklore and mythological subjects. As a result of the analysis of fairy tales and mythical narratives, the authors demonstrate the main function of such heroes who then become participants in plots as supernatural protectors, advisers, mentors, etc. On the basis of theoretical concepts of scientific works that deal with the consideration of the relation of heroes and their patrons, the samples of world and Kazakh verbal art are compared. The analysis of the images of such heroes in the literature has made it possible to make certain conclusions.